KONSEP PEMODELAN TRANSPORTASI UNTUK EVAKUASI BENCANA - ., Hardiansyah; Muthohar, Imam; Priyanto, Sigit; Suparma, Latief Budi (Jurnal Transportasi, 2016)
Abstract The increase of incidence of natural disasters over the past two decades, spawned many ideas about disaster risk reduction impacts both in terms of social and engineering, including in the field of transport evacuation. The rules of scientific developments in the field of transport modeling evacuation typically rely on natural disasters as well as the movement of traffic during the evacuation process. Concept model of transportation for evacuation is divided in two parts, the first focusing on the performance of the road network and the second on the behavior of individual refugees. Based model of transportation refugee behavior has the advantage that individual refugee can be added capabilities and knowledge of the evacuation; only in this concept study is very limited area coverage. Then the concept of performance based transportation model has the advantage of the road network can capture the phenomenon of the movement of traffic as a result of the evacuation on a large scale, in which the main results of simulation in the form of evacuation time and the identification of network vulnerability, only this model require accuracy in data collection, analysis and calibration process. The application of the concept of performance-based model of the road network in the case of disaster evacuation in Indonesia is very applicable at the level set evacuation routes, where the system optimized and user optimized is part of the scenario modeling to optimize its performance. Keywords: model of transportation, disasters, evacuation, network, refugees Abstrak Peningkatan kejadian bencana alam selama dua dasawarsa terakhir melahirkan banyak gagasan mengenai pengurangan dampak risiko kebencanaan baik dari sisi sosial maupun teknis, termasuk pada bidang transportasi evakuasi. Perkembangan kaidah keilmuan dalam bidang pemodelan transportasi evakuasi bergantung pada tipikal bencana alam serta pergerakan lalulintas saat proses evakuasi. Konsep model transportasi untuk evakuasi dibagi dua bagian, pertama fokus pada kinerja jaringan jalan dan kedua pada perilaku individu pengungsi. Model transportasi berbasis perilaku pengungsi memiliki keuntungan, yaitu individu pengungsi dapat ditambahkan kemampuan dan pengetahuan akan evakuasi, hanya pada konsep ini cakupan wilayah kajiannya sangat terbatas (mikro). Kemudian konsep model transportasi berbasis kinerja jaringan jalan memiliki keuntungan dapat menangkap fenomena pergerakan lalulintas akibat proses evakuasi dalam skala besar, di mana hasil utama simulasi berupa waktu evakuasi dan identifikasi jalur padat, hanya saja model ini memerlukan kecermatan dalam pengumpulan data, proses analisis, dan kalibrasinya. Adapun penerapan konsep model berbasis kinerja jaringan jalan untuk kasus evakuasi bencana di Indonesia sangat aplikatif pada tataran menetapkan rute evakuasi, di mana system optimized dan user optimized merupakan bagian dari skenario pemodelan untuk mengoptimalkan kinerjanya. Kata kunci: model transportasi, bencana, evakuasi, jaringan, pengungsi